The Composition of The Foraging Habitat of Bats (Pteropodidae) in Three Urban Open Spaces in South Tangerang City - Hidayah, Khohirul; Meidiyanto, Meidiyanto; Wijayanti, Fahma; Handayani, Nurul (Al-Kauniyah: Jurnal Biologi, 2025)
Pteropodidae bats play an important role in seed dispersal and plant pollination in urban areas. This study aims to identify microclimate factors and forage plant phenology that influence the selection of foraging habitats of Pteropodidae bats in three Green Open Spaces of South Tangerang City. Bat captures were conducted using mist nets placed purposively, for 3 nights with 2 mist nets each in 3 different habitat types. The analysis used was Canonical Correspondence Analysis (CCA) using Canoco software version 4.5. The results found 4 types of Pteropodidae bats, namely Cynopterus brachyotis, Cynopterus horsfieldii, Cynopterus titthaecheilus, and Macroglossus sobrinus. A total of 28 species from 18 plant families were identified that have the potential to be used as food for Pteropodidae bats in South Tangerang City. Based on the results of the analysis using Canonical Correspondence Analysis (CCA), the microclimate factors that influence foraging preferences are the level of disturbance and 3 groups have different tendencies in choosing foraging habitats.